The Role of Auditors in Prevention of Fraud under Corporate Governance Process - V. Suresh Kumar, M.; Ch. Lakshmana Rao, Dr. (International Journal of Engineering and Technology, 2019)
Corporate governance has emerged as a big issue in corporate sector due to the scams and scandals that are taking place to maintain equilibrium between economic and public goals individually and collectively.The present paper is concerned with the role of Auditors as stake holders in corporate governance process and the importance of each Auditor in detection and prevention of fraud as stakeholder in knowing about the disclosure level in the corporate governance process.The overall conclusion of the paper is that stakeholders primarily auditors should contribute their portion with responsibility as it represents value frame work, ethical frame work, and moral frame work of the present-day global business.Â Â Â